2009
DOI: 10.1021/ie800940e
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized-Bed Coating with Sodium Sulfate and PVA−TiO2, 1. Review and Agglomeration Regime Maps

Abstract: This paper, and two associated papers Bach, P. Ind. Eng. Chem. Res. 2009, 48, 1905 and 1914, address the fluid-bed coating of placebo enzyme granules (i.e., sodium sulfate cores, with a size range of 400-500 µm) using two types of coatings: sodium sulfate and PVA-TiO 2 . The coating experiments were conducted in a medium-scale top-spray MP-1 fluid bed, and many rheological experiments were performed on the coating formulations to support the interpretation of the fluid-bed coating results. In this first part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…The agglomeration tendencies are statistical similar in the three experiments with coating solution G; the three agglomeration percentages are within the a range of (0.88%, as determined for the sieve equipment in the first part of this study. 2 The situation is different for the experiments with coating solution A, because there are significant differences between the agglomeration percentages. In accordance with expectations, the agglomeration tendency decreases as the mean droplet size decreases.…”
Section: Testing the Influence Of Bulk Viscosity Of The Coating Solutmentioning
confidence: 99%
See 2 more Smart Citations
“…The agglomeration tendencies are statistical similar in the three experiments with coating solution G; the three agglomeration percentages are within the a range of (0.88%, as determined for the sieve equipment in the first part of this study. 2 The situation is different for the experiments with coating solution A, because there are significant differences between the agglomeration percentages. In accordance with expectations, the agglomeration tendency decreases as the mean droplet size decreases.…”
Section: Testing the Influence Of Bulk Viscosity Of The Coating Solutmentioning
confidence: 99%
“…The three coating solutions were solutions A, B, and C, which were described in the first part of this series of reports. 2 Two coating experiments were performed for each coating solution for two sets of drying force/spray rate conditions, according to Table 3. Lastly, the influence of additives in the PVA-TiO 2 system will be tested.…”
Section: Bulk Viscosity Of the Coating Solutions Stickiness And Thementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in pan coating, a coating solution is sprayed to urea granules under air high temperature for drying purposes [ 88 ]. This often results in poor coating quality (defective porous layer) due to poor maintenance of the humidity level during production [ 89 ]. It was also reported that coating uniformity using this method is affected by particle size distribution, binder properties, the number of coating materials and drying temperature [ 27 ].…”
Section: Coating Techniquesmentioning
confidence: 99%
“…Modification of PVA with LA can have several benefits on resulting polymer material, including that esterification of PVA secondary hydroxyl groups with LA may decrease its hydrophilicity and PVA/LA interactions increase intermolecular spacing among PVA chains [15][16][17]. It means that LA acts in PVA systems as a plasticizer [5,[18][19][20], which is also interesting from a mechanical properties point of view.…”
Section: Introductionmentioning
confidence: 99%